Stability of exact solutions of the cubic-quintic nonlinear Schrödinger equation with periodic potential - Kengne, E.; Vaillancourt, R. (Нелінійні коливання, 2010)
The nonlinear Schrodinger equation with attractive quintic nonlinearity in periodic potential in 1D, modelling a dilute gas Bose – Einstein condensate in a lattice potential, is considered and one family of exact
stationary solutions is discussed. Some of these solutions have neither an analog in the linear Schrodinger
equation nor in the integrable nonlinear Schrodinger equation. Their stability is examined analytically and
numerically. Розглянуто нелiнiйне рiвняння Шредiнгера з притягуючою нелiнiйнiстю п’ятого порядку в одновимiрному перiодичному потенцiалi, яке моделює розряджений газовий конденсат Бозе – Ейнштейна в решiтчатому потенцiалi, а також деяку сiм’ю точних стацiонарних розв’язкiв. Деякi з цих розв’язкiв не мають аналогiв серед розв’язкiв нi лiнiйного рiвняння Шредiнгера, нi
iнтегровного нелiнiйного рiвняння Шредiнгера. Дослiджено стабiльнiсть таких розв’язкiв аналiтичними та чисельними методами.